THE EFFECT OF POST-TENSIONED FLAT PLATES ON SEISMIC BEHAVIOR OF CONCRETE STRUCTURES - EDREES , LARA; ISSA, MOHAMAD (Journal of Duhok University, 2023)
Due to rapid population growth and limited construction space, high-rise buildings have been commonly used to overcome this problem. Post-tensioned flat slabs are widely utilised in this type of structures majorly, because of their light weight and low floor height. These buildings must effectively resist lateral loads which are more critical in this case. Therefore, this paper aims to analyse and compare the seismic behavior of post-tensioned flat plate buildings with that of conventional flat plate buildings. Time period, story drifts, and frames' moments and forces are studied and their results are compared. Response spectrum method is employed in the analysis. The results indicated that the post-tensioning system is more effective than the conventional concrete system.